Highly Efficient Visible-Light-Driven [2+2] Cycloaddition of Maleimides to Alkenes and Alkynes for the Synthesis of 3-Azabicyclo[3.2.0]heptane-Fused Scaffolds - He, Jian; Liu, Qiang (Synthesis, 2021)
A highly efficient [2+2] cycloaddition between maleimides and unsaturated moieties, utilizing a visible-light triplet sensitization mode, has been developed for the direct synthesis of multifunctional 3-azabicyclo[3.2.0]heptane derivatives. This reaction relies on selective activation of the maleimide functionality upon energy transfer from a new photosensitizer that outperforms diverse well-established photosensitizers. The strategy developed herein overcomes previous obstacles such as limited substrate scope and undesired reaction pathways under harsh UV irradiation.
Keywords: visible light sensitization; energy transfer; photocatalysis; cycloadditions; 3-azabicyclo[3.2.0]heptanes